Evaluasi Tingkat Keberhasilan Dukungan Sistem Informasi Kuliah Kerja Nyata - Bisri, Achmad; Jamridafrizal; Kania, Raden; Solihati, Tifani Intan (Teknik Informatika Fakultas Ilmu Komputer, 2026)
This study evaluates the success of the Kukerta Information System using a structured questionnaire covering eight key dimensions. The results show that the system meets the criteria of a successful information system, with most respondents giving Good or Very Good ratings. System Quality achieved an average score of 3.52, indicating ease of use and clarity, though response speed can still improve. Information Quality received the highest score at 3.67, reflecting accuracy and relevance. Service Quality averaged 3.60, showing generally helpful technical support. The Use dimension scored 3.62, demonstrating active utilization, while User Satisfaction reached 3.64 due to reliable system performance. Individual Impact scored 3.65, indicating enhanced user productivity. Organizational Impact and Net Benefits both averaged 3.64, showing improved coordination and benefits that exceed constraints. Overall, the system provides strong performance, useful information, and positive effects for users and the organization.